Digital Image Correlation (DIC) technique in measuring strain using opensource platform Ncorr - Ab Ghani, Ahmad Fuad; Ali, Mohd Basri; Dhar Malingam, Sivakumar; Mahmud, Jamaluddin (Penerbit Akademia Baru, 2020)
This paper presents a systematic explanation on procedure and method of digital image correlation (DIC) technique in utilizing open source platform Ncorr. The use of digital image correlation in measuring strain is shown from its initial stage of speckle preparation on surface of gauge area, acquisition of images through video imaging, splitting the images, and postprocessing the image correlation to obtain displacement and strain field on surface under study. Some technical issues relating the quality of results to be obtained are discussed. Validation of output obtained from strain measurement using Ncorr has been performed via tensile test on GFRP with comparison of modulus of elasticity obtained from experimental. Limitation of using in house equipment such as DSLR camera with considerably low frame per second capability and resolution has given the prospect of high reliability of low cost strain measurement using high speed camera and integrated load cell data acquisition for recommendation and future research activity.